Photoresponsiveness affects life history traits but not oxidative status in a seasonal rodent - Anna S. Przybylska (Frontiers in Zoology, 2019)
Abstract Background Shortening photoperiod triggers seasonal adjustments like cessation of reproduction, molting and heterothermy. However there is a considerable among-individual variation in photoresponsiveness within one population. Although seasonal adjustments are considered beneficial to winter survival, and natural selection should favor the individuals responding to changes in photoperiod (responders), the phenotype non-responding to changes in day length is maintained in population. Assuming the same resource availability for both phenotypes which differ in strategy of winter survival, we hypothesized that they should differ in life history traits. To test this we compared reproductive traits of two extreme phenotypes of Siberian hamster Phodopus sungorus – responding and non-responding to seasonal changes in photoperiod. We bred individuals of the same phenotype and measured time to first parturition, time interval between litters, offspring body mass 3, 10 and 18 days after birth and their growth rate. We also analyzed nest-building behavior. Additionally, we estimated the correlation between reproduction, and basal metabolic rate (BMR) and oxidative status in both phenotypes to infer about the effect of reproductive output on future investments in somatic maintenance. Results Prior to reproduction responding individuals were smaller than non-responding ones, but this difference disappeared after reproduction. Responding pairs commenced breeding later than non-responding ones but there was no difference in time interval between consecutive litters. Responders delivered smaller offspring than non-responders and more out of responding individuals built the nest during winter than non-responding ones. Reproduction did not affect future investments in somatic maintenance. Phenotypes did not differ in BMR and oxidative status after reproduction. However, concentration of reactive oxygen metabolites (ROM) was highest in responding males, and biological antioxidant potential (BAP) was higher in males of both phenotypes than in females. Conclusions Delayed breeding in responding Siberian hamsters and high ROM concentration in male responders support our hypothesis that differences in adjustment to winter result in different life history characteristics which may explain coexistence of both phenotypes in a population. We propose that polymorphism in photoresponsiveness may be beneficial in stochastic environment, where environmental conditions differ between winters. We suggest that non-responding phenotype may be particularly beneficial during mild winter, whereas responders would be favored under harsh conditions. Therefore, none of the phenotypes is impaired when compared to the other.